Biocompatibility Assessment of PLCL-Sericin Copolymer Membranes Using Wharton's Jelly Mesenchymal Stem Cells - Kewalin Inthanon; Donraporn Daranarong; Pimwalan Techaikool; Winita Punyodom; Vorathep Khaniyao; Audrey M. Bernstein; Weerah Wongkham (Hindawi Limited, 2016)
Stem cells based tissue engineering requires biocompatible materials, which allow the cells to adhere, expand, and differentiate in a large scale. An ideal biomaterial for clinical application should be free from mammalian products which cause immune reactivities and pathogen infections. We invented a novel biodegradable poly(L-lactic-co-ε-caprolactone)-sericin (PLCL-SC) copolymer membrane which was fabricated by electrospinning. Membranes with concentrations of 2.5 or 5% (w/v) SC exhibited qualified texture characteristics with a noncytotoxic release profile. The hydrophilic properties of the membranes were 35-40% higher than those of a standard PLCL and commercial polystyrene (PS). The improved characteristics of the membranes were due to an addition of new functional amide groups, C=O, N-H, and C-N, onto their surfaces. Degradation of the membranes was controllable, depending on the content proportion of SC. Results of thermogram indicated the superior stability and crystallinity of the membranes. These membranes enhanced human Wharton's jelly mesenchymal stem cells (hWJMSC) proliferation by increasing cyclin A and also promoted cell adhesion by upregulating focal adhesion kinase (FAK). On the membranes, hWJMSC differentiated into a neuronal lineage with the occurrence of nestin. These data suggest that PLCL-SC electrospun membrane represents some properties which will be useful for tissue engineering and medical applications.